2022
DOI: 10.1186/s12958-022-00995-2
|View full text |Cite
|
Sign up to set email alerts
|

linc00958/miR-185-5p/RSF-1 modulates cisplatin resistance and angiogenesis through AKT1/GSK3β/VEGFA pathway in cervical cancer

Abstract: Background Chemoresistance is one of the major obstacles that lead to poor prognosis in cervical cancer. linc00958 was reported to be an oncogene in cervical cancer. However, its role in mediating chemoresistance remains to be revealed. Purpose To explore the regulatory mechanisms of linc00958 in cisplatin-resistant cervical cancer cells and further validate in xenograft mice. Methods Online bioinforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…It is interesting to note that KEGG pathway enrichment was observed only in the downregulated group (Figure 5F; Table S3). Among these enrichments, some signaling pathways were commonly related to cisplatin resistance in osteosarcomas, such as the mitogen‐activated protein kinase (MAPK) pathway 20‐24 and vascular endothelial growth factor (VEGF) 25‐27 . Additionally, 10 hub genes were identified, and their associated signaling pathways were demonstrated (Figure 5G).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is interesting to note that KEGG pathway enrichment was observed only in the downregulated group (Figure 5F; Table S3). Among these enrichments, some signaling pathways were commonly related to cisplatin resistance in osteosarcomas, such as the mitogen‐activated protein kinase (MAPK) pathway 20‐24 and vascular endothelial growth factor (VEGF) 25‐27 . Additionally, 10 hub genes were identified, and their associated signaling pathways were demonstrated (Figure 5G).…”
Section: Resultsmentioning
confidence: 98%
“…Among these enrichments, some signaling pathways were commonly related to cisplatin resistance in osteosarcomas, such as the mitogen‐activated protein kinase (MAPK) pathway 20 , 21 , 22 , 23 , 24 and vascular endothelial growth factor (VEGF). 25 , 26 , 27 Additionally, 10 hub genes were identified, and their associated signaling pathways were demonstrated (Figure 5G ). These hub genes also appeared to play a regulatory role in reducing cisplatin resistance when ITGB3 was knocked out (Figure 5G ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, linc00958 expression was correlated with a short survival in cervical cancer patients. Mechanistically, linc00958 regulated miR-185-5p and RSF-1 and modulated cisplatin resistance in cervical cancer cells via targeting AKT1/GSK3β/VEGFA pathway ( Tian et al, 2022 ). Depletion of lncRNA NCK1-AS1 promoted cisplatin sensitivity to cisplatin via modulating miR-134-5p and restoring the expression of MSH2 in cervical cancer ( Zhang et al, 2019 ).…”
Section: Other Lncrnas Regulate Drug Resistancementioning
confidence: 99%
“…Moreover, an increasing number of studies have demonstrated that lncRNAs may participate in the regulation of DDP sensitivity in cervical cancer. For example, Tian et al reported that linc00958 expression was upregulated in DDP-resistant cervical cancer cells, and linc00958/miR-185-5p/RSF-1 contributed to DDP resistance and angiogenesis through AKT1/GSK3β/VEGFA signaling in cervical cancer (Tian et al, 2022). In addition, Liu et al provided the evidence that lncRNA NNT-AS1 facilitated DDP resistance of cervical cancer by targeting miR-186/HMGB1 signaling cascade (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tian et al. reported that linc00958 expression was upregulated in DDP‐resistant cervical cancer cells, and linc00958/miR‐185‐5p/RSF‐1 contributed to DDP resistance and angiogenesis through AKT1/GSK3β/VEGFA signaling in cervical cancer (Tian et al., 2022). In addition, Liu et al.…”
Section: Introductionmentioning
confidence: 99%